CCHN: Centro de Ciências Humanas e Naturais - Borges Corte, Viviana; Artem dos Santos, Ana Julia; Guimarães Saraiva, Fernanda; Silva Clarindo Torteloti, Simone; Garcez Moura, Paulo Rogerio; Oliveira Sabbagh, Daniel; de Oliveira Bezerra, Lucas; Silva Braucks Calazans, Luana; Ferreira Dutra, Valquíria; Toso Alexandre, Daniel; Carvalho, Sidinei; Marchioro, Eberval; et al. (Revista Guará, 2023)
Resumos dos projetos do Centro de Ciências Humanas e Naturais